Deletion of Interleukin-6 Attenuates Pressure Overload-Induced Left Ventricular Hypertrophy and Dysfunction. Issue 12 (10th June 2016) - Zhao, Lin; Cheng, Guangming; Jin, Runming; Afzal, Muhammad R.; Samanta, Anweshan; Xuan, Yu-Ting; Girgis, Magdy; Elias, Harold K.; Zhu, Yanqing; Davani, Arash; Yang, Yanjuan; Chen, Xing; et al.
Abstract : Rationale: : The role of interleukin (IL)-6 in the pathogenesis of cardiac myocyte hypertrophy remains controversial. Objective: : To conclusively determine whether IL-6 signaling is essential for the development of pressure overload–induced left ventricular (LV) hypertrophy and to elucidate the underlying molecular pathways. Methods and Results: : Wild-type and IL-6 knockout ( IL-6 −/− ) mice underwent sham surgery or transverse aortic constriction (TAC) to induce pressure overload. Serial echocardiograms and terminal hemodynamic studies revealed attenuated LV hypertrophy and superior preservation of LV function in IL-6 −/− mice after TAC. The extents of LV remodeling, fibrosis, and apoptosis were reduced in IL-6 −/− hearts after TAC. Transcriptional and protein assays of myocardial tissue identified Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and signal transducer and activator of transcription 3 (STAT3) activation as important underlying mechanisms during cardiac hypertrophy induced by TAC. The involvement of these pathways in myocyte hypertrophy was verified in isolated cardiac myocytes from wild-type and IL-6 −/− mice exposed to prohypertrophy agents. Furthermore, overexpression of CaMKII in H9c2 cells increased STAT3 phosphorylation, and exposure of H9c2 cells to IL-6 resulted in STAT3 activation that was attenuated by CaMKII inhibition. Together, these results identify the importance of CaMKII-dependent activation of STAT3 during cardiac myocyte hypertrophy via IL-6 signaling. Conclusions: : Genetic deletion of IL-6 attenuates TAC-induced LV hypertrophy and dysfunction, indicating a critical role played by IL-6 in the pathogenesis of LV hypertrophy in response to pressure overload. CaMKII plays an important role in IL-6–induced STAT3 activation and consequent cardiac myocyte hypertrophy. These findings may have significant therapeutic implications for LV hypertrophy and failure in patients with hypertension. Abstract : Supplemental Digital Content is available in the text.